HUBUNGAN ANTARA MODEL PEMBELAJARAN KOOPERATIF DAN PENGGUNAAN MEDIA PEMBELAJARAN MULTIMEDIA DENGAN MINAT BELAJAR SISWA PADA PELAJARAN PENDIDIKAN AGAMA ISLAM - Purwanto (Balai Diklat Keagamaan Bandung, 2022)
Learning problems occur in Islamic Education is the students’ saturation when participating learning activities and their low interest in studying Islamic education. Other causes include monotonous learning methodologies and learning media. The study aims to determine the relationship between cooperative learning and multimedia learning media with students’ learning interest in Islamic Education. This study uses a quantitative approach with correlational research method. The techniques used in the research are observation, interviews, and questionnaires. The data were analyzed using quantitative techniques aided by Microsoft Office Excel and SPSS 20. The results showed that the correlation coefficient numerical analysis of cooperative learning model with students’ learning interest over the subject is 0.275, obtained a significant correlation and categorized as low correlation. The result of numerical analysis of correlation coefficients in multiimedia learning media with students’ learning interest to the subject is 0,308, implies significant correlation and low category. The relationship between cooperative learning model and multimedia learning media with students’ interest in Islamic Education subject altogether is 0.328, which means significant with low correlation category.